黃藥子 메탄올 추출물의 염증억제 효과 - 정지윤(Ji Yun Jung); 이종록(Jong Rok Lee); 변성희(Sung Hui Byun); 정지욱(Ji Wook Jung); 김용한(Yong Han Kim); 김상찬(Sang Chan Kim) (동의생리병리학회지, 2010)
Dioscorea bulbifera is one of the traditional medicinal herb. It commonly used in the treatment of hematemesis, epistaxis, tuberculous cervical lymphadenitis, laryngitis, acute infectious disease in East Asia. In the present study, we have demonstrated the anti-inflammatory effects of Dioscorea bulbifera MeOH extract (DBME) in macrophage cell line. To investigate mechanism of the anti-inflammatory activity, we examined the effects of the lipopolysaccaride (LPS)-induced production of nitric oxide (NO), prostaglandin E2 (PGE2), pro-inflammatory cytokines and expression of inducible NO synthase (iNOS), cyclooxygenase-2 (COX-2), p-inhibitory κBα (p-IκBα), and nuclear factor-κB (NF-κB) in a murine macrophage cell line RAW 264.7. The RAW 264.7 cells were cultured in DMEM + serum medium for 24 hrs. After serum starvation for 24 hrs, the cells were treated with DBME 0.03, 0.10, 0.30 ㎎/㎖ for 1 h, followed by stimulation with LPS (1 ㎍/㎖) for activation of immune response. After treatment, cell viability was measured by MTT assay, and NO production was monitored by measuring the nitrite content in culture medium. The protein band of iNOS, COX-2, p-IκBα, and NF-κB was determined by immunoblot analysis and levels of cytokine were analyzed by sandwich immunoassays. There were three experimental groups: carrageenan, DBME 0.3, 1.0 g/kg. Rats were administrated either carrageenan (40% PEG) or carrageenan + DBME (0.3, 1.0 g/kg body weight) for 4 days (p.o.). To induce acute paw edema, rats were injected 1% carrageenan (100 ㎕/rat, dissolved in sterilized saline). The effect of DBME in the carrageenan-induced rat paw edema. As results, DBME has an inhibitory effect on the production of NO, PGE2, TNF-α, IL-1β and IL-6 and on the expression of iNOS, COX-2, p-IκBα and translocation of NF-κB to nuclear from cytosol. In addition, DBME effectively inhibited the increases of paw edema induced by carrageenan treatment in vivo. These results suggest that DBME can inhibit production of pro-inflammatory mediators and might be a useful source for treatment of acute inflammatory disease. Dioscorea bulbifera is one of the traditional medicinal herb. It commonly used in the treatment of hematemesis, epistaxis, tuberculous cervical lymphadenitis, laryngitis, acute infectious disease in East Asia. In the present study, we have demonstrated the anti-inflammatory effects of Dioscorea bulbifera MeOH extract (DBME) in macrophage cell line. To investigate mechanism of the anti-inflammatory activity, we examined the effects of the lipopolysaccaride (LPS)-induced production of nitric oxide (NO), prostaglandin E2 (PGE2), pro-inflammatory cytokines and expression of inducible NO synthase (iNOS), cyclooxygenase-2 (COX-2), p-inhibitory κBα (p-IκBα), and nuclear factor-κB (NF-κB) in a murine macrophage cell line RAW 264.7. The RAW 264.7 cells were cultured in DMEM + serum medium for 24 hrs. After serum starvation for 24 hrs, the cells were treated with DBME 0.03, 0.10, 0.30 ㎎/㎖ for 1 h, followed by stimulation with LPS (1 ㎍/㎖) for activation of immune response. After treatment, cell viability was measured by MTT assay, and NO production was monitored by measuring the nitrite content in culture medium. The protein band of iNOS, COX-2, p-IκBα, and NF-κB was determined by immunoblot analysis and levels of cytokine were analyzed by sandwich immunoassays. There were three experimental groups: carrageenan, DBME 0.3, 1.0 g/kg. Rats were administrated either carrageenan (40% PEG) or carrageenan + DBME (0.3, 1.0 g/kg body weight) for 4 days (p.o.). To induce acute paw edema, rats were injected 1% carrageenan (100 ㎕/rat, dissolved in sterilized saline). The effect of DBME in the carrageenan-induced rat paw edema. As results, DBME has an inhibitory effect on the production of NO, PGE2, TNF-α, IL-1β and IL-6 and on the expression of iNOS, COX-2, p-IκBα and translocation of NF-κB to nuclear from cytosol. In addition, DBME effectively inhibited the increases of paw edema induced by carrageenan treatment in vivo. These results suggest that DBME can inhibit production of pro-inflammatory mediators and might be a useful source for treatment of acute inflammatory disease. KCI Citation Count: 3